Peran Siaran Radio, Televisi, Multimedia (Internet) dalam Pengembagan Dakwah - Erwan Efendi; Aviatri Fatimah; Indah Mawati Sipahutar (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Dakwah, on the other hand, is not always a product born from the pulpit. The spread of da'wah messages is now more dynamic and adaptive thanks to the widespread use of media. Modern da'wah is increasingly made possible by the use of mass media by people from all walks of life who want to invite and convey goodness, namely da'wah activities. In online media and social media, such as Instagram, Facebook, You Tube, short films, radio, and so on, a person can convey messages of kindness through writing (kalam), speech, and behavior or actions (objects). This study is descriptive in nature which describes and describes how to manage the fundamental ideas of radio, television and multimedia (internet) with da'wah content that has occurred in Indonesia throughout history and today.. Therefore, in order for the da'wah to be delivered on target, Muslims, preachers, and television producers need to be skilled at managing this media as effectively as possible. Modern information technology must be used to spread Islamic teachings in the global era, both in urban and rural areas. Keywords: Development of Mass Media, Television, Radio, Multimedia, Da'wah.